A Comparative Analysis of Eleventh Grade Students’ Reading Comprehension of Narrative Texts Using Printed and Digital Media at SMA Negeri 9 Sidrap - Rismayanti; Sam Hermansyah; Sitti Aisa; Isumarni (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to examine the differences in eleventh-grade students’ reading comprehension of narrative texts when taught using printed and digital media, as well as to determine which medium is more effective. A quantitative approach with a quasi-experimental design was employed, involving two groups: an experimental group taught using printed media and a control group taught using digital media. The research was conducted at SMA Negeri 9 Sidrap in the 2025/2026 academic year, with a total sample of 36 students selected through purposive sampling. Data were collected using a 20-item multiple-choice reading comprehension test administered as pre-test and post-test. The data were analyzed using descriptive statistics, homogeneity testing, independent sample t-test, and effect size (Cohen’s d). The findings revealed a significant difference between the two groups, with a significance value of 0.001 (p < 0.05). The experimental group achieved a higher mean score (87.78) compared to the control group (77.50). Moreover, the effect size (d = 1.24) indicated a large effect. These results suggest that printed media is more effective than digital media in improving students’ reading comprehension of narrative texts. This study provides empirical evidence for teachers and educators in selecting appropriate instructional media in EFL classrooms.